2011
DOI: 10.1155/2011/901854
|View full text |Cite
|
Sign up to set email alerts
|

Liver Metabolic Alterations and Changes in Host Intercompartmental Metabolic Correlation during Progression of Malaria

Abstract: 1H NMR-based metabonomics was used to investigate the multimodal response of mice to malarial parasite infection by P. berghei ANKA. Liver metabolism was followed by NMR spectroscopy through the course of the disease in both male and female mice. Our results showed alterations in the level of several metabolites as a result of the infection. Metabolites like kynurenic acid, alanine, carnitine, and β-alanine showed significant alteration in the liver, suggesting altered kynurenic acid, glucose, fatty acid and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Metabolomic studies have been reported that are of relevance to Wilson's disease [103, 104], primary biliary cirrhosis [105], primary sclerosing cholangitis [105], the hepatic stage of malaria [106108], as well as various aspects of hepatic encephalopathy [109112]. …”
Section: The Metabolomic Window Into Other Hepatobiliary Diseasesmentioning
confidence: 99%
“…Metabolomic studies have been reported that are of relevance to Wilson's disease [103, 104], primary biliary cirrhosis [105], primary sclerosing cholangitis [105], the hepatic stage of malaria [106108], as well as various aspects of hepatic encephalopathy [109112]. …”
Section: The Metabolomic Window Into Other Hepatobiliary Diseasesmentioning
confidence: 99%
“…Malarial infection was shown to heavily alter peripheral and tissue level metabolite levels [16][17][18][19][20][21][22][23][24][25][26] These studies are carried out after the infections are well established, but alterations in rodent host metabolism during low parasitemia (<1%) are unknown. In RBC cultures at~5% parasitemia, significant alterations in glucose utilization have been observed [14,27], and thus it was of interest to study whether glucose utilization will be affected in the RBCs, liver, and brain of the host during this early stage of malarial infection.…”
Section: Nmr Spectroscopy Of Organ and Cellular Extractsmentioning
confidence: 99%
“…Multiway Principal Component Analysis (MPCA) is used to understand the metabolic correlations between different organs and compartments of the body [31], [32]. Kidney, spleen and serum constitute three different compartments of the body and MPCA gives metabolic correlations that occur across them.…”
Section: Statistical Analyses Of the Datamentioning
confidence: 99%